Reshaping the field: technocratic facts, high wheat yields, and the making of an ecological disaster - Gabriela Soto Laveaga (Tapuya)
Today the Yaqui Valley, a renowned farming region in northern Mexico, is a top emitter of greenhouse gas. Made famous as the birthplace of the Green Revolution, the high-yielding seeds that transformed the world’s farming were engineered in the research station located in the valley. Research led by agronomist Norman Borlaug not only transformed seeds but significantly altered the contemporary understanding of fertilizer use. Five times as much fertilizer as had previously been used became part of the needed recipe to produce high yields of wheat. Decades later, soil and groundwater contamination could be traced to the heavy use of agrochemicals. This article examines pre-1970s writings, both scientific publications and an oral history, to understand how this leap in fertilizer use became normalized and persisted for nearly seven decades.